Research progress on rapeseed green processing technology - ZHANG Xin; REN Yuan-yuan; WANG Bo; MENG Zi-kuan; ZHOU Yu; ZHANG Xin-chan; WANG Yong-jun (Liang you shipin ke-ji, 2020)
Green processing technology has wide prospects in rapeseed industry.The research progress of process technologies including microwave, pulsed electric field, shelling, cold pressing, enzymatic hydrolysis,supercritical CO2 extraction, low temperature green refining combined with the utilization of by-products at home and abroad were introduced, and their application prospects were further prospected.